Sambamba: fast processing of NGS alignment formats - Tarasov, Artem; Vilella, Albert J.; Cuppen, Edwin; Nijman, Isaac J.; Prins, Pjotr (Bioinformatics (Oxford, England), 2015)
Sambamba is a high-performance robust tool and library for working with SAM, BAM and CRAM sequence alignment files; the most common file formats for aligned next generation sequencing data. Sambamba is a faster alternative to samtools that exploits multi-core processing and dramatically reduces processing time. Sambamba is being adopted at sequencing centers, not only because of its speed, but also because of additional functionality, including coverage analysis and powerful filtering capability. Availability and implementation: Sambamba is free and open source software, available under a GPLv2 license. Sambamba can be downloaded and installed from http://www.open-bio.org/wiki/Sambamba. Sambamba v0.5.0 was released with doi:10.5281/zenodo.13200. Contact: j.c.p.prins@umcutrecht.nl